Modelling Malaysian outward foreign direct investment from the home and host countries' perspectives / Rosfadzimi Mat Saad - Mat Saad, Rosfadzimi (Institute of Graduate Studies, UiTM, 2018)
Outward Foreign Direct Investment (OFDI) is one of the measures to indicate the performance and capability of developing countries firms in economic integration where border barriers are eliminated. Malaysia as a developing economy is undertaking OFDI due to the limitation of local resources and to search for new markets. Thus in relation to the contemporary economic development mainly globalisation and regionalism issue, in the context of Malaysia as one of the emerging developing countries, identifying the primary determinants contributed to OFDI of Malaysia is crucial for sustainable growth. This thesis studies the determinants of OFDI by Malaysian based Multinational Corporations, MNCs. It focuses on the trends, patterns and domestic factors that pushes off Malaysian firms to involve in OFDI using Dunning's Push Factors theory. Multiple regression analysis is performed on time series data beginning from 1981 to 2011. The study finds that income level, labour quality, currency value, trade openness, firm's capability and technology are the major pushing factors of Malaysia's OFDI. In addition, the studies also examine Malaysian OFDI in the developing countries perspective as suggested by Banga (2005) before proceeding to the long run dynamic Auto-Regressive Distributed Lag, ARDL model…